Evaluating consumer preferences for reduced cooking time, taste and colour of beans in rural and urban communities in Uganda - Asiimwe, Robert; Katungi, Enid Mbabazi; Marimo, Pricilla; Mukankusi, Clare; Rubyogo, Jean Claude; Anthony, Vivienne (BioMed Central, 2024)
Background Common bean breeders strive to deliver farmer- and consumer-preferred varieties that are well-adapted to distinct production environments, changing markets and end uses. However, there is information gap on the key traits that customers prefer and are willing to pay for. This paper examined the preferences and willingness to pay for reduced cooking time and other selected traits in the Ugandan bean markets using a choice experiment data elicited from 1152 urban and rural bean consuming households. A latent class model was used to assess preferences and the willingness to pay for reduced cooking time. Results Results indicated that taste, cooking time, bean swelling on cooking, and grain color were the preferred attributes in decreasing order among non-bean-producers. About 72% of the urban consumers were willing to pay 41 shillings, 53 shillings and 42 shillings above prices for reduction in cooking time from 120 (status quo) to 90, 75, and 60 min, respectively. For consumers who also grow their beans for food and surplus for sale, reduced cooking time is important but not as much as yield and climate resilience. The study identified four distinct customer segments—two among bean-producing households and two among non-bean-producing households. Gender, education, level of altruism/openness to change, household economic status, and price sensitivity were the major factors influencing segment membership. Conclusions The study findings demonstrated that breeding to reduce cooking time will generate a significant social savings in terms of less cooking fuel, water and time, but cooking time ought to be considered alongside other attributes preferred by consumers and farmers to succeed. Results also suggest that women urban consumers attach more importance to higher levels of intrinsic traits (non-visible but experienced by consumers) compared to men—thus promotional campaigns popularizing new varieties should target women to stimulate demand.